What firm characteristics determine women ' s employment in manufacturing? Evidence from Bangladesh. Issue 2 (14th March 2016) - Ahmed, Salma; Feeny, Simon; Posso, Alberto
Abstract : Purpose: – The purpose of this paper is to investigate the principal determinants of women's employment in the manufacturing sector of Bangladesh using a firm-level panel data from the World Bank's "Enterprise Survey" for the years 2007, 2011 and 2013. The paper sheds light on the demand-side factors, mainly firm-level characteristics, which also influence this decision. Design/methodology/approach: – The authors estimate a fractional logit model to model a dependent variable that is limited by zero from below and one from above. Findings: – The results indicate that firm size, whether medium or large, and firms' export-oriented activities, have an important impact on women's employment in the manufacturing sector in Bangladesh. Moreover, the authors find that women are significantly more likely to work in unskilled-labour-intensive industries within the manufacturing sector. Research limitations/implications: – The research is limited to Bangladesh; however, much of the evidence presented here has implications that are relevant to policymakers in other developing countries. Practical implications: – The study identifies factors that affect female employment, that is, where the main constraints to increase female labour force participation. The study focuses on the demand-side factors, which has been somewhat neglected in recent years. As such, it has practical policy implications. Social implications: – Focusing on female employment in Bangladesh also sheds light on the nexus between labour market opportunities and social change within a country that is characterised by extreme patriarchy, which has wide-reaching implications. Originality/value: – This is an original and comprehensive paper by the authors.